Metabolic reprogramming for cancer cells and their microenvironment: Beyond the Warburg Effect - Sun, Linchong; Suo, Caixia; Li, Shi-ting; Zhang, Huafeng; Gao, Ping (Biochimica et biophysica acta. Reviews on cancer, 2018)
While metabolic reprogramming of cancer cells has long been considered from the standpoint of how and why cancer cells preferentially utilize glucose via aerobic glycolysis, the so-called Warburg Effect, the progress in the following areas during the past several years has substantially advanced our understanding of the rewired metabolic network in cancer cells that is intertwined with oncogenic signaling. First, in addition to the major nutrient substrates glucose and glutamine, cancer cells have been discovered to utilize a variety of unconventional nutrient sources for survival. Second, the deregulated biomass synthesis is intertwined with cell cycle progression to coordinate the accelerated progression of cancer cells. Third, the reciprocal regulation of cancer cell's metabolic alterations and the microenvironment, involving extensive host immune cells and microbiota, have come into view as critical mechanisms to regulate cancer progression. These and other advances are shaping the current and future paradigm of cancer metabolism.